Longitudinal analysis of the incidence rate of injury in elite youth football: Trends over six years including the COVID-19 pandemic period - Škomrlj, J.; Modric, T.; Sekulic, D.; Bandalovic, A.; Turic, A.; Becir, B.; Veršic, Š. (Physical Therapy in Sport, 2024)
Objectives We aimed to analyze injury trends and the possible effects of the coronavirus disease (COVID-19) pandemic on the incidence rates of injury in young elite football players.